An Unusual Case of Hematemesis in a 12-Month-Old. Issue 6 (June 2015) - Mueller, Dana; Schroeder, Luke; Kaila, Rahul; Louie, Jeff
<x xml:space="preserve">Abstract</x> Abstract A 12-month-old male with a history of failure to thrive and hypothyroidism presented to a pediatric emergency department twice in a 24-hour period with complaint of hematemesis. The patient had a recent upper endoscopy and biopsy as part of a work-up for failure to thrive, but had no other pertinent positives in clinical history. Ultrasound demonstrated findings concerning for an intramural duodenal hematoma. The patient was admitted to the gastroenterology service for intravenous hydration and nasogastric decompression. He did not require any invasive management or blood products. Duodenal hematoma is a known, but very uncommon complication of upper endoscopy.